From Evaluation to the Construction of A Sporting Policy For The Benefit Of Local Development: The Case Of The Commune Of Bobo Dioulasso (Burkina Faso) - AKOUETE, CoffiDavid; OUATTARA, Amadou; AHOUNOU AÏKPE, FIFAMIN JUDITH; GOUDA, SOUAÏBOU L.LompoSouaïbou; DANSOU, HOUNDJOVI PIERRE; Haschar-Noe, Nadine (My University, 2020)
In a context of scarcity of resources and constantly growing evolution of the sporting world at the local level, this study aims to analyze the modes of development and implementation of local sporting action in the town of BoboDioulasso, in Burkina Faso. To do this, two survey techniques were used to collect the data. The questionnaire for users and the interview with local elected officials, officials of sports structures and decentralized state services. The results show that sports are an integral part of the habits of the vast majority of local populations. With social demand more focused on sustaining sport, the evaluation of the municipality's actions gives a very vague idea of the local political orientation in matters of sport. In addition to the unsatisfied demand from sports structures, that of unorganized users, with poor structuring of spaces and sports facilities in the middle. For a contribution of physical and sporting activities to the well-being and development of individuals and to the enhancement of their living environment, this study suggests the establishment of a real local sports policy, included in the municipal development policy.
Keywords: physical and sports activities; local communities; public authorities; management; BoboDioulasso.